Research on blockchain: privacy protection of cryptography blockchain-based applications - Dayong, Zhang; Wahab, Nur Haliza Abdul; Kadir, Khairunnisa A.; Aldhaqm, Arafat; Nasir, Haslinah Mohd; Wong, Keng Yinn (2023)
Blockchain is a distributed database technology developed because of cryptocurrency, which has the characteristics of open and transparent ledger data. However, attackers will analyze ledger data to obtain sensitive information, threatening transaction privacy of users. Cryptography is the underlying technology of the blockchain to ensure the integrity and legitimacy of transactions in the blockchain. Providing privacy protection for the blockchain by studying cryptography has become a research hotspot in the blockchain. This paper introduces the cryptography technology in the blockchain, summarizes the privacy protection problems existing in the current blockchain, and expounds the existing cryptography solutions and the advantages and disadvantages of each scheme. Finally, the future research directions of cryptography in blockchain are summarized and prospected.